Ladakh: diverse, high-altitude extreme environments for off-earth analogue and astrobiology research. Issue 1 (13th February 2020) - Pandey, Siddharth; Clarke, Jonathan; Nema, Preeti; Bonaccorsi, Rosalba; Som, Sanjoy; Sharma, Mukund; Phartiyal, Binita; Rajamani, Sudha; Mogul, Rakesh; Martin-Torres, Javier; Vaishampayan, Parag; Blank, Jennifer; et al.
Abstract: This paper highlights unique sites in Ladakh, India, investigated during our 2016 multidisciplinary pathfinding expedition to the region. We summarize our scientific findings and the site's potential to support science exploration, testing of new technologies and science protocols within the framework of astrobiology research. Ladakh has several accessible, diverse, pristine and extreme environments at very high altitudes (3000–5700 m above sea level). These sites include glacial passes, sand dunes, hot springs and saline lake shorelines with periglacial features. We report geological observations and environmental characteristics (of astrobiological significance) along with the development of regolith-landform maps for cold high passes. The effects of the diurnal water cycle on salt deliquescence were studied using the ExoMars Mission instrument mockup: HabitAbility: Brines, Irradiance and Temperature (HABIT). It recorded the existence of an interaction between the diurnal water cycle in the atmosphere and salts in the soil (which can serve as habitable liquid water reservoirs). Life detection assays were also tested to establish the best protocols for biomass measurements in brines, periglacial ice-mud and permafrost melt water environments in the Tso-Kar region. This campaign helped confirm the relevance of clays and brines as interest targets of research on Mars for biomarker preservation and life detection.